Measuring and Evaluating the Fulfillment of Competence Management and People Development System Criteria in Accordance with ISO 10015:2019 – A Case Study of Baghdad Municipality - Mohammed Thaer Ali; Raoudha Kammoun (Migration Letters, 2023)
The objective of this study is to assess the extent to which the Municipality of Baghdad complies with the requirements outlined in ISO 10015: 2019 for competency management system and personnel development. This will be achieved by conducting a gap analysis, which involves measuring and analyzing the disparity between the current state of affairs in the municipality and the stipulations of the ISO standard. To accomplish this objective, a case study methodology was employed, and a checklist was utilized as a tool for measuring the identified gaps. The checklist pertaining to the gathering of data and information was officially endorsed, and a workshop was conducted with officials undergoing training in order to guarantee the attainment of precise data accessibility. A total of 98 questions were included in the list, covering all items specified. Frequencies, percentages, and averages were subsequently computed. The computation was given a higher importance as the chosen method for interpreting the data. The findings of the study indicate that the implementation of the competency management system and personnel development in the Municipality of Baghdad, in relation to the standard requirements, has achieved a level of 72%. This suggests that the system is almost fully implemented but lacks proper documentation. Consequently, there exists a gap of 28% that can be addressed through ongoing improvements, management evaluation of the system, resolution of documentation concerns, and fulfillment of specific requirements.